Potential interplay of the Gatipotuzumab epitope TA-MUC1 and estrogen receptors in ovarian cancer - Heublein, Sabine; Marmé, Frederik (International journal of molecular sciences, 2019)
Anti-tumor efficacy of Gatipotuzumab, a therapeutic antibody targeting Tumor-Associated Mucin-1 (TA-MUC1), in relapsed ovarian cancer (OC) appeared to be rather heterogeneous. Whether adding a second anti-neoplastic drug may augment response towards Gatipotuzumab, has not been elucidated so far. Since it is known that anti-MUC1 antibodies may alter estrogen receptor activity in breast cancer, this potential interplay was investigated in OC. The correlation between TA-MUC1, estrogen receptors (ERs) and another 12 protein markers as well as their correlation with clinico-pathological parameters in 138 ovarian cancer cases was studied. Finally, Gatipotuzumab and 4-Hydroxy-TTamoxifen (4-OHT) as well as the combination of both was tested for its impact on cell viability in COV318, OV-90, OVCAR-3, and SKOV-3 cells. A strong positive correlation between TA-MUC1 and ERs was detected in OC tissue. Those cases missing ERs but staining positive for TA-MUC1 had significantly reduced overall survival. The combination of 4-OHT and Gatipotuzumab significantly reduced cell viability and was more effective than treatment with Gatipotuzumab alone. Co-stimulation with Gatipotuzumab enhanced the efficacy of 4-OHT in OVCAR-3 and SKOV-3. The data suggest an interplay of TA-MUC1 and ERs in OC. Whether the combination of Gatipotuzumab and TTamoxifen may enhance efficacy of either of the two drugs in vivo, or may even translate into a clinically relevant benefit over the respective monotherapies, remains to be investigated.
Gesehen am 23.01.2019